Al-Dacwah Al-Fardīiyyah: Discourse on its Action Plan - BAHARI, CHE AMNAH; FAISAL, MUHAMMAD (Journal of Islam in Asia (E-ISSN 2289-8077), 2012)
The al-dacwah al-fardīyyahseems to be very significant in making Islamic message reach the targets. Action plan of this technique has been developed by various scholars based on Ḥasan al-BannÉ’sthought. This action plan has beenproven to be an effective one until today.This article focuses mainly on four dimensions of the issue: (1) the definitionof al-dacwah al-fardīyyah, (2) the history of al-dacwah al-fardīyyah, (3) the differences between al-dacwah al-fardīyyah and al-cÉmmah, and (4) the current developments in the work of al-dacwah and itsaction plan.